Couples' narratives of shared‐self, possessions and consumption experiences. Issue 1 (3rd October 2016) - Wong, Phoebe; Hogg, Margaret K.; Vanharanta, Markus
Abstract: How consumers use possessions and consumption to enact their shared‐self has been underexplored in earlier consumer research. The purpose of this paper is to investigate the emergence of couple‐level (or partnered) shared‐self. A narrative research method was used in Hong Kong, which allowed for an inter‐temporal narrative about the informants' important possessions. Our findings revealed key characteristics regarding the way in which informants' interpretations of shared selves developed over time. This included sharing and negotiating resources (e.g., a house or money) with their partners, integrating similar perspectives (e.g., interests and lifestyle) to their partners', and including their partners as part of the self. This study provides the basis for future research to see how these findings hold up at other stages of partnered relationships. This research provides a conceptualization – a temporal model of couples' shared‐self – that could contribute to and enhance the existing literature on the interrelationship between possessions and the extended self. Copyright © 2016 John Wiley & Sons, Ltd.